Penerapan Hukum dalam Tindak Pidana Penipuan dan Penggelapan Terkait Jaminan Fidusia - Waskito, Indra; Sabrina, Nahdiya (MLJ Merdeka Law Journal, 2024)
Fiduciary is a process of transferring ownership rights to an object based on trust, provided that the object remains in the control of the owner of the object. The implementation of this form of engagement is a hire purchase agreement between the creditor and the debtor, where this engagement does not always run smoothly. There are times when the debtor commits embezzlement, namely by deliberately transferring the hand of the fiduciary collateral object without the creditor's permission. The purpose of this research is to examine the application of legal regulations to debtors who commit criminal acts of fraud and embezzlement related to fiduciary guarantees and the basis for consideration by Supreme Court Judge Number 485 K/Pid/2020. The research method used is normative juridical. The results of this research include that in the Fiduciary Guarantee Law there are criminal sanctions for debtors (fiduciary givers) who commit acts of transferring fiduciary collateral objects without prior approval from the fiduciary recipient (creditor). Meanwhile, in the Criminal Code it is included in the crime of embezzlement, namely Article 372. The basis for the judge's consideration in deciding the case is 1). Whereas the defendant has been proven to have harmed the victim witness; 2). The defendant did not return the victim's losses.